Willingness to use long-acting injectable pre-exposure prophylaxis (LAI-PrEP) among black cisgender women in the Southern United States - Sylvia Shangani; Jaquetta M. Reeves; Kristin Heron; Jessica M. Sales; Kenneth K. Mugwanya (PLoS ONE, 2025)
Background Long-acting injectable pre-exposure prophylaxis (LAI-PrEP) for HIV prevention may improve adherence for those with concerns with daily pills. Limited data exist on LAI-PrEP acceptability among Black women in the U.S., a population vulnerable to HIV. We assessed willingness to use LAI-PrEP among Black women eligible for PrEP in the Southern U.S. Methods We conducted a cross-sectional online survey of HIV-negative Black women from March to June 2022 in the U.S. South. Participants provided information on sociodemographic characteristics, HIV knowledge, PrEP awareness, and use, stigma, risk perception, medical mistrust, and healthcare access. Multivariate logistic regression models determined factors associated with willingness to use LAI-PrEP. Results Of 491 women, the mean (SD) age was 40.1 (17.5), 53% of participants had a college degree or lower, 79% were single, and 80% resided in urban/suburban settings. Thirty-nine percent were aware of PrEP before the study and 36.7% of women were willing to use LAI-PrEP. In multivariate analyses, PrEP awareness [adjusted odds ratio (aOR=2.37, 95% CI 1.40, 3.73, p < 0.001), having a personal clinician (aOR=2.01, 95% CI 1.10, 3.68, p = 0.02), HIV worried (aOR=1.78, 95% CI 1.09, 2.89, p = 0.02), and medical trust (aOR=1.41, 95% CI 1.03, 1.93, p = 0.04) were statistically associated with willingness to use LAI-PrEP. However, the healthcare stereotype (beliefs that healthcare is biased) had lower odds of using LAI-PrEP (aOR=0.94, 95% CI 0.89, 0.99, p = 0.04). Conclusion Black women at risk for HIV are more likely to consider injectable PrEP when they understand HIV risk factors, are aware of PrEP, have a clinician, and trust the medical care. Implementing client-centered care interventions could effectively address medical mistrust and enhance engagement in HIV prevention services among Black women.